The Commodification of The Candle Festival of Ubonratchathani - ตันติเศรษฐ กฤตยภรณ์ (Thai Interdisciplinary and Sustainability Review, 2019)
This research concerns dynamics of commodification of candle festival of Ubonratchathani. The research has done by using qualitative approach research documents related including the study about cultural history and the origin of candle festival up to the present and structure interview guideline, participatory non-participatory observations, tourism and the relative of candle festival Ubonratchathani up to now to understand about commodification of candle festival which is in belief, adoration of Buddhism which have been since the old Age. They are cultural material and hide in the Buddha story that putting the light up for giving alms by using an idea of process to make a produce of Marxist Institution for analyzing and linking to culture capital by the result of the research finding that the culture of candle festival Ubonratchathani is different in each Age which is relevant with the structure and Thai social context at that moment.